THE LEXICO GRAMMATICAL FEATURES OF THE POLITICAL REGISTER ANALYSIS IN THE EDITORIAL OF THE JAKARTA POST NEWSPAPER - Yana, Dewi (JURNAL DIMENSI, 2012)
The registers are the arrangement of meaning which is characteristic by changes in relation to the condition of use. Thus the researcher is also interest to analyze what are actually the meanings of political register based on the context or situation. There are two types of meaning found in the sentences written in the editorial of  The Jakarta Post Newspaper. Those two types of meaning are conceptual meaning and reflective meaning. There were no connotative, stylistic, affective, collocative and thematic types of meaning found in this research.